Technology for weed management in jute - Ghorai, A. K.; Chowdhury, H.; Kumar, Mukesh; Kumar, Shailesh (Indian Farming, 2015)
Jute seedlings are very small, delicate and grow slowly during initial 30 days and consequently can not compete with weeds. It caused 40-70% yield loss if not controlled properly. Weeds in jute can be effectively managed by cultural practices like intercrop with Amaranthus or Raphanus spp, manually by hand weeding or wheel hoeing and chemically by application of butachlor, pretilachloras preemergence and quizalofop-ethyl as post-emergence herbicide. These herbicides alone or in combination followed by one hand weeding or hoeing at 35 days after sowing has been found to be very effective and economical to control the weeds in jute field.